Neuromyelitis optica spectrum disorder after post appendectomy peritonitis: A case report - Muhammad Zaid, MBBS; Fatima Saleemi, MBBS; Rana Muhammad Usama, MBBS; Ayman Tahir, MBBS; Aima Azhar, MBBS; Mohammed Mahmmoud Fadelallah Eljack, MBBS; Muhammad Junaid Tahir, MBBS (Radiology Case Reports, 2024)
Neuromyelitis optica spectrum disorder (NMOSD), also known as “Devic's syndrome”, is an autoimmune demyelination disorder. It affects the optic nerve and spinal cord, causing optic neuritis and transverse myelitis. It is associated with anti-aquaporin 4 antibodies that target the aquaporin channel on astrocytes. An 18-year-old male with a history of appendectomy 6 months ago presented with neck pain, numbness in limbs up to the umbilicus, paresis, and spasticity in the left leg. The brain magnetic resonance imaging (MRI) was normal, while the spinal cord MRI showed hyperintense foci at the T2 level. Cerebrospinal fluid (CSF) analysis was in the normal range and negative for oligoclonal bands. The serological assay was positive for anti-aquaporin-4 antibodies (AQP4-IgG). The patient improved significantly after administering high doses of methylprednisolone and supplements. Due to the unavailability of eculizumab, he underwent plasmapheresis sessions to remove antibodies, which improved to a reasonable extent. NMOSD most commonly targets older females, but in our report, it appeared in a young male. The patient only presented with transverse myelitis with no ophthalmologic problem. He made significant improvement with combination treatment of steroids, supplements, and plasmapheresis.